The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4082/kjfm.18.0054
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Mammography Adoption among Women in Iran: A Qualitative Study

Abstract: Background: Breast cancer is the most commonly diagnosed tumorous cancer and the second leading cause of cancer-related deaths among women worldwide. This study aimed to qualitatively explore the barriers to mammography adoption among Iranian women. Methods: This study is a qualitative component of a large research project on exploratory sequential mixed method design, utilizing conventional content analysis. In total, 24 participants were selected from among women who had participated in the first phase of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…27,28 A study conducted in the United States among Jordanian and Palestinian immigrant women revealed that the respondents experienced certain fears such as fear of cancer treatment, fear of pain, and fear of cancer discovery. 29 Shirzadi et al 30 showed that perception of mammography harmfulness was an established barrier towards MS as the women experienced their worries about radiation exposure in addition to the fear of the procedure itself. 30 Overcoming of the personal barriers can be done by enhancing health-seeking behavior in the awareness campaigns through informing the women about 2558 the benefits of early recognition of BC and empowering them to take care of own health even if they were busy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 A study conducted in the United States among Jordanian and Palestinian immigrant women revealed that the respondents experienced certain fears such as fear of cancer treatment, fear of pain, and fear of cancer discovery. 29 Shirzadi et al 30 showed that perception of mammography harmfulness was an established barrier towards MS as the women experienced their worries about radiation exposure in addition to the fear of the procedure itself. 30 Overcoming of the personal barriers can be done by enhancing health-seeking behavior in the awareness campaigns through informing the women about 2558 the benefits of early recognition of BC and empowering them to take care of own health even if they were busy.…”
Section: Discussionmentioning
confidence: 99%
“…29 Shirzadi et al 30 showed that perception of mammography harmfulness was an established barrier towards MS as the women experienced their worries about radiation exposure in addition to the fear of the procedure itself. 30 Overcoming of the personal barriers can be done by enhancing health-seeking behavior in the awareness campaigns through informing the women about 2558 the benefits of early recognition of BC and empowering them to take care of own health even if they were busy. In addition, these awareness campaigns should provide all the information necessary about MS to the women.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of awareness is one of the most prominent barriers to screening in different countries [15,16,23,24,34,58,59,61,62,83]. Low level of awareness about breast cancer and its diagnostic methods [16,25,35,61], advantages of early detection of breast cancer, the necessity and importance of screening, the time of screening [25], knowledge of how to perform screening, clinics available in the city and consequences of late detection of breast cancer justify the low prevalence of mammography screening in many Asian countries [26, 36-38, 61, 63, 64, 84]. In a study in Turkey, those who had information about mammography were eight times more likely to perform screening than those who did not have information [27], (OR ¼ 8.83, 95% CI: 3.27, 23.84).…”
Section: -1 Knowledgementioning
confidence: 99%
“…While there is a growing body of research on a barriers such as lack of knowledge, fear of breast cancer diagnosis, 8 , 9 possible pain experienced during mammography, low self-efficacy, lack of health motivation, lack of access to health-care, and lack of physician referral, 10 - 12 research on the role of fear of negative evaluation on mammography screening is scarce. Due to its consequences, 13 - 15 fear of negative evaluation would be an important detrimental factor in women’s mammography screening.…”
Section: Introductionmentioning
confidence: 99%